(untitled) (KONFERENSIYA, 2026)
This article analyzes the structural aspects of translation equivalence in English–Uzbek journalistic discourse. Journalistic texts can involve particular challenges because of their orientation functional orientation, genre-specific features and sociocultural context. The research focuses on structural differences between two languages including word order, grammatical categories, sentence complexity, and headline instruction and analyzes how these factors affect the achievement of translation equivalence. Using a comparative descriptive approach, selected examples from news reports and opinion articles are analyzed to identify common translation strategies such as syntactic transformation, grammatical compensation and functional adaptation. The article concludes that successful English–Uzbek journalistic translation requires a balance between preserving structural elements of the source text and adapting them to the linguistic and stylistic norms of Uzbek.